Konsep Kepribadian Seorang Muslimah Milenial Pada Era Revolusi Industri (Telaah Buku Amazing Stories) - Marlina, Marlina; Tasari, Reni; Tasdiq, M (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
In this modern and advanced era, the challenges of becoming a pious Muslim woman are much greater and more difficult. Personality means a series of normative human behavior, the norms of which are derived from the Koran, Sunnah and Ijtihad. An increasingly advanced civilization could also be a factor in the collapse of morals and morals. The progress and decline of Islamic generations cannot be separated from women. So there is a need for a female figure to be a role model, namely Fatimah Az-Zahra. Fatimah is a role model and exemplary example in her great qualities. The method used in this research is a qualitative research method, a type of library study research using content analysis. Muslim women are respected and given honor in Islam. Taking care of oneself, cleansing one's morals, covering one's private parts, wearing a hijab and dressing respectably are very noble and beautiful attitudes for Muslims. The character of Fatimah Az-Zahra greatly influences the development and personality of Muslim women in the current era. And Fatimah Az-Zahra's character can be a role model for shaping good human behavior for the development of her personality.